2018
DOI: 10.3892/ijmm.2018.3376
|View full text |Cite
|
Sign up to set email alerts
|

Cynandione�A inhibits lipopolysaccharide-induced cell adhesion via suppression of the protein expression of VCAM‑1 in human endothelial cells

Abstract: Cynandione A (CA) is one of the most active compounds in the roots of Cynanchum wilfordii, the extracts of which have been used extensively in East Asia to treat various diseases including anti‑ischemic stroke. In the present study, the anti‑adherent activity of CA in lipopolysaccharide (LPS)‑stimulated human umbilical vascular endothelial cells (HUVECs) was investigated. CA markedly reduced the expression of vascular adhesion molecule‑1 (VCAM‑1) by LPS in HUVECs. The results also demonstrated that CA signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…IL-6, TNF-␣, and IL-1␤ are crucial inflammatory factors in the initiation and progression of cardiovascular diseases. Additionally, expression of endothelial adhesion molecules, which is induced by proinflammatory cytokines, plays an important role in vascular endothelial cell injury and leads to vascular disease (17). In the present study, we observed that LPS stimulation dramatically elevated the secretion of several proinflammatory cytokines such as IL-6, TNF-␣, IL-1␤, and MCP-1.…”
Section: Discussionsupporting
confidence: 59%
“…IL-6, TNF-␣, and IL-1␤ are crucial inflammatory factors in the initiation and progression of cardiovascular diseases. Additionally, expression of endothelial adhesion molecules, which is induced by proinflammatory cytokines, plays an important role in vascular endothelial cell injury and leads to vascular disease (17). In the present study, we observed that LPS stimulation dramatically elevated the secretion of several proinflammatory cytokines such as IL-6, TNF-␣, IL-1␤, and MCP-1.…”
Section: Discussionsupporting
confidence: 59%
“…Eventually the leukocytes break through the endothelial barrier and reach lesion site. Under normal physiological conditions, endothelial cells are inactive and do not express adhesion molecules, but under pathological conditions (such as BBB damage), a large number of exogenous cytokines are generated and the endothelial cells are activated, so that VCAM-1 is expressed (Park et al, 2018). VCAM-1 on the surface of endothelial cells mediates leukocyte adhesion through its interaction with VLA-4, which consists of CD49d (α4) and CD29 (β1).…”
Section: Discussionmentioning
confidence: 99%
“…The ethanolic extract of CW increases blood HDL-C levels and reduces the atherogenic index although there was no significant difference in total cholesterol in the high-cholesterol diet SD rats and apoE −/− mice [23]. In this study, CW was standardized with cynandione A which was reported to have anti-inflammatory effects by inhibiting VCAM-1 in human endothelial cells or inhibiting MAPK and NF-κB in macrophages [17,18]. Besides cynandione A, CW has been identified to have various phytochemicals such as dihydroxyacetophenone, acetovanillone, conduritol F, geniposide, bungeiside A and β-sitosterol [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…Cynandione A has been reported to prevent ischemic stroke by regulating the pathway associated with thrombotic or embolic occlusion [16]. Cynandione A also exhibits anti-inflammatory effects by inhibiting VCAM-1 in human endothelial cells or inhibiting MAPK and NF-κB in macrophages [17,18]. Caudatin isolated from CW also exhibits antifungal activity [19].…”
Section: Introductionmentioning
confidence: 99%